Respuesta :

is it possible for you a little flame to do it again and i’m

Answer:

x = 1

Step-by-step explanation:

The proportion in this question is (3z) : (3z)+(z+22) = (2x+1) : (8x-2), since there are two triangles that are similar.

The question said that 3z = z+22

--> 2z = 22

--> z = 11

So our new proportion will be:

--> (3z) : (3z)+(z+22) = (2x+1) : (8x-2)

--> (33):(66) = (2x+1):(8x-2)

--> (66)(2x+1) = (33)(8x-2)

--> 132x + 66 = 264x - 66

--> 132x - 132 = 0

--> 132x = 132

--> x = 1